2003
DOI: 10.1159/000074058
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Spreading of Topically Applied UV Filter Substances Investigated by Tape Stripping

Abstract: The lateral spreading of topically applied substances is a competitive process to the penetration into the stratum corneum (SC). The penetration of topically applied UV filter substances into the human SC and the lateral spreading were investigated in vivo. Tape stripping in combination with spectroscopic measurements was used to study both processes of two UV filter substances. The concentration of both UV filters was determined inside and outside the application area by varying the application and tape strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
(25 reference statements)
5
31
0
Order By: Relevance
“…Meanwhile, the percentage of urea distributed outside the application area was symmetric in this study (fig. 3) - similar to results shown by Jacobi et al [19]. The symmetric surface structure of the skin, consisting of a network of furrows, could be the reason for this result.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Meanwhile, the percentage of urea distributed outside the application area was symmetric in this study (fig. 3) - similar to results shown by Jacobi et al [19]. The symmetric surface structure of the skin, consisting of a network of furrows, could be the reason for this result.…”
Section: Discussionsupporting
confidence: 88%
“…3) show that 18.4% (solution) and 13.4% (cream) of topically applied urea can spread outwards from the application site after 6 h. In addition, the amount of substance found outside the application area seems dependent on the size of the area [19]. Relatively small application areas are usually used so it is important to take lateral spreading into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weigmann et al showed this for the penetration of the drug clobetasol-propionate [64]. The behaviour of sunscreens applied on human skin was investigated using tape stripping, too [65,66]. However, to our knowledge, until now tape stripping in combination with MS was not used for the analysis of UV generated molecular changes within skin with or without sunscreens.…”
Section: Quantificationmentioning
confidence: 99%